Latin American Women Artists: Subsidiary Human Beings? The Latin American Women Artists, 1915–1995 case - Gluzman, Georgina Gabriela (2024)
In 1995, the exhibition "Latin American Women Artists, 1915–1995" opened at the Milwaukee Art Museum. This exhibition marked the first-ever survey of Latin American women artists organised in the United States. Curated by Geraldine Pollack Biller, the show included works by thirty-five women artists active in eleven Latin American countries. This article aims to analyse the categories (“women artists”, “Latin American art”, and “Latin American women artists”) adopted by the exhibition and to examine some of the artists whose works were exhibited. What artists were selected? What were the implications of the selection? Did it reinforce certain stereotypes associated with Latin America and its art? Informed by feminist and Latin American art theories, deconstructing Euro-American notions of Latin American art, I argue that the emphasis on women artists did not significantly change the perception of Latin American art as “fantastic”. The thesis presented by anthropologist Sherry B. Ortner in 1974, which suggests that women have been traditionally linked with nature while men are associated with culture, can be illuminating when applied to comprehending the Latin American exotic cliché presented by the exhibition. Women were seen as doubly subsidiary human beings (in Rivolta Femminile’s words): non-Western and members of the second sex.